Physiological responses of young tennis players to training drills and simulated match play - Gomes, R. V.; Cunha, V. C. R.; Zourdos, M. C.; Aoki, M. S.; Moreira, A.; Fernandez-Fernandez, J.; Capitani, C. D. (The Journal of Strength and Conditioning Research, 2016)
The aim of this study was to investigate the responses of young tennis players during 5 different training drills and to compare the responses between drills. Ten (17.0 ± 1.2 years) male tennis players participated in this study. Each athlete completed 5 total training drills. Drills 1-4 consisted of each player returning balls from a ball-serving machine and were stroke/time-controlled over 6 points. The fifth drill was a simulated match (SM) play, between 2 opposing players, and also lasted 6 points. The 4 stroke/time-controlled drills had the following strokes/time for each point: drill 1: 2 strokes/~4 seconds, drill 2: 4 strokes/~8 seconds, drill 3: 7 strokes/~14 seconds, drill 4: 10 strokes/~20 seconds. Peak heart rate (HR), blood lactate concentration (LA), and rating of perceived exertion (RPE) were measured after the first, third, and sixth point of each drill. Drills were performed in a randomized crossover design; a 2-way repeated-measures analysis of variance was used with significance set at p = 0.05. All dependent variables (HR, LA, and RPE) significantly increased (p = 0.05) as strokes, and time per rally increased in each drill. Furthermore, all variables were elevated to a greater magnitude (p = 0.05) during the 7 and 10 stroke drills after the first, third, and sixth points when compared with the SM and the 2 and 4 stroke drills at the corresponding time points. These results suggest that the physiological responses to tennis training drills were stroke/time-dependent. Therefore, because of the intense intermittent nature of tennis, stroke/time-controlled drills, which require significant physiological demands, should be incorporated along with technically focused shorter drills to fully mimic the conditions of competitive match play.